I’m not sure if the expression should be for the cost, which can be shown by:
(9/4)x - 3 = total cost of the items, where x is the cost of a sandwich.
For the items individually,
(1/4)x = y, where y is the cost of a bag of chips.
x - 3 = z, where z is the cost of a soda.
Combining each individual expression, it becomes:
x + y + z = total cost.
(x) + ((1/4)x) + (x-3) = total cost
= (9/4)x - 3
This assumes Jordan and his friends bought a sandwich + soda + bag of chips.
You could try writing without variables to help picture the expression:
(1/4)sandwich = bag of chips
and
sandwich - $3 = soda
If x represents the cost of a sandwich, this can be rewritten as:
x + x - 3 + (1/4)x
There are like terms with x, so it can simplify further: (9/4)x - 3 = total cost of the items.
Hopefully this makes sense!